DNA Damage Response Proteins and Oxygen Modulate Prostaglandin E2 Growth Factor Release in Response to Low and High LET Ionizing Radiation - Allen, Christopher P.; Tinganelli, Walter; Sharma, Neelam; Nie, Jingyi; Sicard, Cory; Natale, Francesco; King, Maurice; Keysar, Steven B.; Jimeno, Antonio; Furusawa, Yoshiya; Okayasu, Ryuichi; Fujimori, Akira; et al. (Frontiers in Oncology, 2015)
Common cancer therapies employ chemicals or radiation that damage DNA. Cancer and normal cells respond to DNA damage by activating complex networks of DNA damage sensor, signal transducer, and effector proteins that arrest cell cycle progression, and repair damaged DNA. If damage is severe enough, the DNA damage response (DDR) triggers programed cell death by apoptosis or other pathways. Caspase 3 is a protease that is activated upon damage and triggers apoptosis, and production of prostaglandin E2 (PGE2), a potent growth factor that can enhance growth of surviving cancer cells leading to accelerated tumor repopulation. Thus, dying tumor cells can promote growth of surviving tumor cells, a pathway aptly named Phoenix Rising. In the present study, we surveyed Phoenix Rising responses in a variety of normal and established cancer cell lines, and in cancer cell lines freshly derived from patients. We demonstrate that IR induces a Phoenix Rising response in many, but not all cell lines, and that PGE2 production generally correlates with enhanced growth of cells that survive irradiation, and of unirradiated cells co-cultured with irradiated cells. We show that PGE2 production is stimulated by low and high LET ionizing radiation, and can be enhanced or suppressed by inhibitors of key DDR proteins. PGE2 is produced downstream of caspase 3 and the cyclooxygenases COX1 and COX2, and we show that the pan COX1–2 inhibitor indomethacin blocks IR-induced PGE2 production in the presence or absence of DDR inhibitors. COX1–2 require oxygen for catalytic activity, and we further show that PGE2 production is markedly suppressed in cells cultured under low (1%) oxygen concentration. Thus, Phoenix Rising is most likely to cause repopulation of tumors with relatively high oxygen, but not in hypoxic tumors. This survey lays a foundation for future studies to further define tumor responses to radiation and inhibitors of the DDR and Phoenix Rising to enhance the efficacy of radiotherapy with the ultimate goal of precision medicine informed by deep understanding of specific tumor responses to radiation and adjunct chemotherapy targeting key factors in the DDR and Phoenix Rising pathways.